Pseudocapsule of Small Renal Cell Tumors: CT Imaging Spectrum and Correlated Histopathological Features - Li, Gang; Lu, Xianqi; Ding, Yunsheng; Luo, Qiang; Xu, Liang; Zhu, Dongsheng; Quan, Changyi (Urology Journal, 2020)
Purpose: To systematically analyze histopathologic features of pseudocapsule in small renal cell tumor (diameter≤4cm), assess the integrity of pseudocapsules by Computed Tomography (CT), and provide theoretical basis for the safety of nephron sparing surgery. Materials and Methods: The pathological data of 116 patients who underwent surgery with clear cell renal cell carcinoma admitted from May 2010 to October 2017 were retrospectively analyzed. All patients underwent a CT scan of the abdomen including an unenhanced and triple-phase (arterial, nephrographic and excretory) post contrast series."All patients underwent a CT scan of the abdomen including an unenhanced and triple-phase (arterial, nephrographic and excretory) post contrast series."All patients underwent a CT scan of the abdomen including an unenhanced and triple-phase (arterial, nephrographic and excretory) post contrast seriesAll patients underwent a CT scan of the abdomen including an unenhanced and three-phase (arterial, nephrographic and excretory) post contrast series. Thorough gross examination and histological sections were used to determine the integrity of the pseudocapsule by two uropathologists. The consistency between pathological findings and CT imaging were evaluated by Kappa consistency test. Results: The mean diameter of tumor was 3.0cm, range (2.6 ± 0.8) cm. On CT the pseudocapsule can present with one of the three following feathers:1) A regular and distinct halo; 2)lobulated clear margins;3) blurred margins. On histopathology, complete psuedocapsule was found in 85 tumors, incomplete psuedocapsule in 25 and no psuedocapsule was found in 6 tumors; CT scan findings demonstrated a regular halo in 82 tumors, lobulated clear margins in 26 and blurred margins in 8 tumors(Kappa=0.833,P=0.000). Conclusions: Most small renal cell tumors have an obvious psuedocapsule. Preoperative determination of the psuedocapsule’s integrity is particularly important. CT scan can reliably evaluate the tumor margins and demonstrate the psuedocapsule when present. The imaging results are well correlated with the pathologic findings.